The DFG Viewer for Interoperability in Germany - Goebel, Ralf; Meyer, Sebastian (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
This article deals with the DFG Viewer for Interoperability, a free and open source web-based viewer for digitised books, and assesses its relevance for interoperability in Germany. First the specific situation in Germany is described, including the important role of the Deutsche Forschungsgemeinschaft (German Research Foundation). The article then moves on to the overall concept of the viewer and its technical background. It introduces the data formats and standards used, it briefly illustrates how the viewer works and includes a few examples.